Postpolymerization of a 3D-printed denture base polymer: Impact of post-curing methods on surface characteristics, flexural strength, and cytotoxicity. (December 2021) - Li, Ping; Lambart, Anna-Lena; Stawarczyk, Bogna; Reymus, Marcel; Spintzyk, Sebastian
Abstract: Objective: This study investigated the influence of postpolymerization of a three-dimensional (3D) printed denture base polymer. The effect of post-curing methods on surface characteristics, flexural strength, and cytotoxicity was evaluated. Methods: A total of 172 specimens were additively manufactured using one denture base material (V-Print dentbase, VOCO) and further post-cured by different light-curing devices, including Otoflash G171 (OF), Labolight DUO (LL), PCU LED (PCU), and LC-3DPrintbox (PB), respectively. Polymethyl methacrylate resin (PalaExpress Ultra) was used as a reference (REF). Afterward, surface topography was observed using scanning electron microscopy, and surface roughness was measured ( n  = 6). Furthermore, flexural strength was tested ( n  = 20). Cytotoxicity was evaluated by the extract and direct contact tests. The data were analyzed using the Kolmogorov-Smirnov test and one-way ANOVA followed by Tukey's multiple comparisons and Kruskal-Wallis tests ( p  < 0.05). Results: The different post-curing methods applied did not significantly influence surface topography and roughness (Ra). Meanwhile, specimens post-cured by PCU (162.3 ± 44.16 MPa) and PB (171.2 ± 34.41 MPa) showed significantly higher flexural strength than those post-cured by OF (131.3 ± 32.87 MPa) and REF (131.2 ± 19.19 MPa), respectively. Additionally, various post-curing methods effectively decreased the cytotoxic effects of 3D-printed denture base polymer. Conclusions: Different post-curing methods did not significantly alter the Ra values of the 3D-printed denture base material. However, flexural strength was significantly affected by the postpolymerization methods, which might be attributed to the different wavelengths of post-curing devices. In addition, various postpolymerization methods reduced the cytotoxic effects of the 3D-printed denture base polymer. Clinical significance: Flexural strength of additively manufactured denture bases depends on the postpolymerization strategy. Therefore, an appropriate post-curing method is required to optimize the flexural strength of 3D-printed denture materials. Graphical abstract: Image, graphical abstract